The Influence Of Competence And Work Motivation On Teacher Performance at SMPN 1 Rindingallo - Sappedatu, Alda (Indonesian Journal of Educational Technology, 2025)
This study aims to examine the effect of teacher competency and work motivation on teacher performance at SMP Negeri 1 Rindingallo, both individually and simultaneously. A quantitative research design was employed using a questionnaire-based survey. The population of this study consisted of all teachers at SMP Negeri 1 Rindingallo, totaling 30 respondents, and the entire population was used as the research sample. The research instrument was a structured questionnaire measuring teacher competency, work motivation, and teacher performance. Prior to hypothesis testing, the data were confirmed to meet the assumptions of normality, homogeneity, and the absence of multicollinearity and autocorrelation.The results of the multiple linear regression analysis indicate that teacher competency has a positive and significant effect on teacher performance (β = 1.144; t = 5.214 > 2.048; p < 0.001). In contrast, work motivation does not have a significant partial effect on teacher performance (β = −0.359; t = −1.670 < 2.048; p = 0.106). However, when examined simultaneously, teacher competency and work motivation have a significant effect on teacher performance, as indicated by the F-test results (F = 17.868 > 3.35; p < 0.05). These findings demonstrate that teacher competency plays a dominant role in improving performance, while work motivation contributes meaningfully when combined with competency.